(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The foremost purpose of this paper is to analyse the impact of the bonus issue on the price of the share of the company. This paper will also appraise the impacts of the price of share by the distribution ratio of bonus shares of pharmaceutical companies. For these study 32 pharmaceutical companies listed in National Stock Exchange & Bombay Stock Exchange has taken which dispersed the bonus issues to its shareholders over the period of 10 years. The sample size of the paper is 32 Indian pharmaceutical companies. The simple random technique has been used by the researchers as a sampling technique for the study and the paper is based on secondary data. The study reveals that the stock price of most of the companies rises next day of bonus issue announcement day. Many pharmaceutical companies distributed bonus shares in the ratio ofmore than or equal to 100 percent responses positively in the study. This study shows that around 65.62 % pharmaceutical companies responses optimistic to the stock prices of the respective stock next day of the bonus announcement. The study also demonstrates that around 43.75% pharmaceuticals companies whose distribution ratio of bonus share is more than or equal to 100 percent deliver a positive return. The highest number of pharmaceutical companies declares the bonus issue in 2013.